A comparative test of the gamete dynamics theory for the evolution of anisogamy in Bryopsidales green algae - Tatsuya Togashi (Royal Society Open Science, 2021)
Gamete dynamics theory proposes that anisogamy arises by disruptive selection for gamete numbers versus gamete size and predicts that female/male gamete size (anisogamy ratio) increases with adult size and complexity. Evidence has been that in volvocine green algae, the anisogamy ratio correlates positively with haploid colony size. However, green algae show notable exceptions. We focus on Bryopsidales green algae. While some taxa have a diplontic life cycle in which a diploid adult (=fully grown) stage arises directly from the zygote, many taxa have a haplodiplontic life cycle in which haploid adults develop indirectly: the zygote first develops into a diploid adult (sporophyte) which later undergoes meiosis and releases zoospores, each growing into a haploid adult gametophyte. Our comparative analyses suggest that, as theory predicts: (i) male gametes are minimized, (ii) female gamete sizes vary, probably optimized by number versus survival as zygotes, and (iii) the anisogamy ratio correlates positively with diploid (but not haploid) stage complexity. However, there was no correlation between the anisogamy ratio and diploid adult stage size. Increased environmental severity (water depth) appears to drive increased diploid adult stage complexity and anisogamy ratio: gamete dynamics theory correctly predicts that anisogamy evolves with the (diploid) stage directly provisioned by the zygote.